2001
DOI: 10.1016/s0146-6410(01)00155-7
|View full text |Cite
|
Sign up to set email alerts
|

Flavor asymmetry of light quarks in the nucleon sea

Abstract: A surprisingly large asymmetry between the up and down sea quark distributions in the nucleon has been observed in recent deep inelastic scattering and Drell-Yan experiments. This result strongly suggests that the mesonic degrees of freedom play an important role in the description of the parton distributions of the hadronic sea. In this article, we review the current status of our knowledge of the flavor structure of the nucleon sea. The implications of various theoretical models as well as possible future me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(70 citation statements)
references
References 182 publications
(235 reference statements)
0
69
1
Order By: Relevance
“…A major surprise in the flavor structure of the nucleon sea was found when deep-inelastic scattering (DIS) and Drell-Yan experiments showed that theū andd in the proton have strikingly different Bjorken-x dependence [1][2][3][4][5][6]. Theoretical models which can explain this flavor asymmetry also have specific predictions on other aspects of spin and flavor structures of sea quarks.…”
Section: Introductionmentioning
confidence: 99%
“…A major surprise in the flavor structure of the nucleon sea was found when deep-inelastic scattering (DIS) and Drell-Yan experiments showed that theū andd in the proton have strikingly different Bjorken-x dependence [1][2][3][4][5][6]. Theoretical models which can explain this flavor asymmetry also have specific predictions on other aspects of spin and flavor structures of sea quarks.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the observation of an excessd overū antiquarks in the proton [23], which has been described in terms of a nπ + configuration [24], might alternately be described in terms of an [udud]d component in the proton. While the N * (1440) may contain significant N π and ∆π components, its unusual properties might also be described in terms of admixtures of colored quark cluster configurations.…”
mentioning
confidence: 99%
“…The reason becomes clear if one compares the predictions of the CQSM with those of the naive meson cloud convolution model. As is widely known, the NMC observationd(x) −ū(x) > 0 in the proton can be explained equally well by the CQSM and by the meson cloud model [68], [69], [70]. A simple intuitive argument, however, indicates that the latter model would generally predict both of ∆ū(x) and ∆d(x) is small.…”
Section: Su(2) Cqsm Su(3) Cqsm Experimentsmentioning
confidence: 86%